Different microplastics distinctively enriched the antibiotic resistance genes in anaerobic sludge digestion through shifting specific hosts and promoting horizontal gene flow. (1st January 2023) - Luo, Tianyi; Dai, Xiaohu; Chen, Zhijie; Wu, Lan; Wei, Wei; Xu, Qiuxiang; Ni, Bing-Jie
Highlights: Elevated level of ARGs is induced by MPs in anaerobic sludge digestion. PVC-MPs induces a greater increase of ARGs abundance than PE-MPs. PE- and PVC-MPs enrich ARB of Acinetobacter sp. and Salmonella sp. PVC-MPs drives the ARGs acquisition by specific bacteria but PE-MPs doesn't. PE- and PVC-MPs enhance horizontal gene flow based on functional profiles. Abstract: Both microplastics (MPs) and antibiotic resistance genes (ARGs) are intensively detected in waste activated sludge (WAS). However, the distinctive impacts of different MPs on ARGs emergence, dissemination, and its potential mechanisms remain unclear. In this study, long-term semi-continuous digesters were performed to examine the profiles of ARGs and antibiotic-resistant bacteria (ARB) in response to two different typical MPs (polyethylene (PE) and polyvinyl chloride (PVC)) in anaerobic sludge digestion. Metagenomic results show that PE- and PVC-MPs increase ARGs abundance by 14.8% and 23.6% in digester, respectively. ARB are also enriched by PE- and PVC-MPs, Acinetobacter sp. and Salmonella sp. are the dominant ARB. Further exploration reveals that PVC-MPs stimulates the acquisition of ARGs by human pathogen bacteria (HPB) and functional microorganisms (FMs), but PE-MPs doesn't. Network analysis shows that more ARGs tend to co-occur with HBP and FMs after MPs exposure, and more importantly, new bacteria are observed to acquire ARGs possibly via horizontal gene flow (HGF) in MPs-stressed digester. The genes involved in the HGF process, including reactive oxygen species (ROS) production, cell membrane permeability, extracellular polymeric substances (EPS) secretion, and ATP synthesis, are also enhanced by MPs, thereby attributing to the promoted ARGs dissemination. These findings offer advanced insights into the distinctive contribution of MPs to fate, host, dissemination of ARGs in anaerobic sludge digestion. Graphical abstract: Image, graphical abstract